WEWENANG PEMERINTAH DAERAH DALAM PENERTIBAN PEREDARAN MINUMAN KERAS DI KOTA CILEGON: Cilegon's City Government Authority On Liquor Distribution Curbing - Rafly Tri Adi; Wiratno (Reformasi Hukum Trisakti, 2024)
The Cilegon City Government has prohibited the sale of alcoholic drinks with an alcohol content above 10%. The impacts of selling alcoholic beverages include social inequality, increased alcohol-related crime, and risks to future generations. The problem formulation in this research focuses on local government policies regarding the challenges faced by officers in controlling alcohol distribution, and how the government overcomes these challenges. The research method uses normative legal methods, descriptive analysis, and data collection through interviews, observation, and documentation studies, with primary and secondary data. Conclusions are drawn deductively. The results of the research and discussion show that based on Article 18 which states "The Mayor has the right to regulate alcoholic beverages", the Cilegon City government is committed to eradicating the distribution of alcoholic beverages by issuing Regional Regulation No. 5 of 2001 concerning Liquor Violations. This regulation is a guide in controlling producers and consumers of alcoholic beverages. In conclusion, the main challenges in controlling alcohol distribution are financial constraints and limited human resources, especially law enforcement officers. Apart from that, the lack of severe sanctions in these regulations is not effective enough to provide a deterrent effect for violators